BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Management of Threatening Plant Diseases of National Importance, Editors, V.P. Agnihotri, A.K. Sarbhoy and D.V. Singh, Publishers Malhotra Publishing House, New Delhi, 314 x iii pp, 1997. The Actinolaims, Predatory Soil NematodesÂ From India (1994) by Zakaullah Khan andÂ Shamim Jairajpuri published by Aligarh MuslimÂ University is mainly a compilation of redescription of nineteen and proposal of tweleve newÂ species suported with good illustrations belongingÂ to Actinolaimoidea Thome, 1939: Dorylaimida :Â Nematoda. Â